2012
DOI: 10.5812/jhs.4532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Upper Limb Musculoskeletal Loads due to Posture, Repetition, and Force by Rapid Upper Limb Assessment in a Textile Factory

Abstract: This article pays attention to the application of an ergonomic risk factors assessment technique so-called "Rapid Upper Limbs Assessment (RULA)" for evaluation of the upper limb musculoskeletal loads due to posture, repetition and force in textile factory. It introduces a practical topic in ergonomics field that can be useful for ergonomists, occupational hygienists, occupational therapists, industrial designers, physiotherapists, rehabilitation specialists, and anthropologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The RULA tool was previously tested for validity and reliability, with appropriate adjustments made 24 . The RULA was used in numerous studies among professions that predominantly use the upper extremities, including the dental professions 13,14,23,26 …”
Section: Methodsmentioning
confidence: 99%
“…The RULA tool was previously tested for validity and reliability, with appropriate adjustments made 24 . The RULA was used in numerous studies among professions that predominantly use the upper extremities, including the dental professions 13,14,23,26 …”
Section: Methodsmentioning
confidence: 99%
“…with proper preventive measures at the structural, organizational, and personnel levels to increase the safety of industrial workers especially those performing hard tasks, these traumas could be prevented (17).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies concluded that high levels of risk were present in their results and therefore there was a need to take corrective actions, in some cases immediately. They agreed that the affected body areas included the torso, neck and arms, amongst others [108,113].…”
Section: Textile Manufacturementioning
confidence: 99%